1993
DOI: 10.5694/j.1326-5377.1993.tb137528.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascertaining the true incidence of stroke: experience from the Perth Community Stroke Study, 1989–1990

Abstract: ObjectiveTo determine the age and sex specific incidence, and case fatality of stroke in Perth, Western Australia. Design and settingA population‐based descriptive epidemiological study. SubjectsAll residents of a geographically defined segment of the Perth metropolitan area (population 138 708) who had a stroke or transient ischaemic attack between 20 February 1989 and 19 August 1990, Inclusive. Main outcome measuresDefinite acute “first‐ever‐in‐a‐lifetime” (first‐ever) and recurrent stroke classified accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(46 citation statements)
references
References 27 publications
4
42
0
Order By: Relevance
“…The 12-month rate for MI, stroke, and GI bleed was low in all exposure groups, consistent with rates in the general population for $50-year-olds (MI: 1.1/100 person-years, 28 stroke: 0.2/100 person-years, 29 GI bleeds: 0.1/100 personyears). 30 We observed no significant differences in the rates of MI, stroke, or GI bleeding between patients treated with bevacizumab or ranibizumab (1.6 and 2.1 events/100 persons, respectively).…”
Section: Discussionsupporting
confidence: 79%
“…The 12-month rate for MI, stroke, and GI bleed was low in all exposure groups, consistent with rates in the general population for $50-year-olds (MI: 1.1/100 person-years, 28 stroke: 0.2/100 person-years, 29 GI bleeds: 0.1/100 personyears). 30 We observed no significant differences in the rates of MI, stroke, or GI bleeding between patients treated with bevacizumab or ranibizumab (1.6 and 2.1 events/100 persons, respectively).…”
Section: Discussionsupporting
confidence: 79%
“…2). Information on timing of scanning was documented in a number of different ways; one study gave a value for the mean time interval from stroke to scanning for those patients who underwent neuroimaging [9]; two studies gave the median time interval from symptoms to scanning [42,7]; but the majority of studies simply documented the proportion of patients scanned within a certain time interval, which ranged from seven days [20,12,3], to 21 days [11] and 30 days [25,4,1,29,34]. No study explicitly stated exactly what proportion of patients were scanned and when (i. e. percent within one week, or two weeks, or three weeks after stroke) making it impossible to estimate what proportion were scanned outside the time when CT would have distinguished infarct from haemorrhage reliably.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing use of magnetic resonance imaging has revealed that it is not uncommon to find evidence of old, apparently asymptomatic small haemorrhages in the brains of elderly patients [27,13] so older patients might also have more small symptomatic PICH. Thus it may be that older people are particularly at risk of PICH, and thus there may be a higher proportion of PICH in this Oxford [4] 1988 Rapidity of death, too ill to transfer, refusal, 65 % of those not scanned > 75 years Malmo [20] 1992 'Mean age of those examined by CT less than those not' Perth [1] 1993 Rapidity of death, too ill, too frail, refusal, 81 % of those not scanned > 75 years Brisbane [33] 1995 'coma, lack of facility, too sick, age of the patient, attitude of the physicians' L'Aquila [7] 1997 Very early death, refusal, exclusive home care of very old patients, equipment breakdown Tartu [26] 1997 'Of the 24 % with no subtype (i. e. no scan), 76 % treated at home Erlangen [25] 1998…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have emphasized the beneficial effects of estrogen in gender differences in I/R injury [5,6], some others have implicated male sexual hormones [7][8][9]. Androgen hormone deficiency and blockade improves survival in male rodents in systemic inflammatory conditions [3,20]. Park et al shown that the presence of testosterone, rather than the absence of estrogen, appears to be more relevant to the gender difference in susceptibility to kidney I/R injury.…”
Section: Discussionmentioning
confidence: 95%
“…Men are at a relatively increased risk of cardiovascular and neurological disorders when compared premenopausal women [3,4]. In general, the gender disparity has been interpreted primarily as reflecting estrogen-mediated protection against pathological conditions [5,6].…”
Section: Introductionmentioning
confidence: 98%